PENGAWASAN DANA DESA OLEH INSPEKTORAT KABUPATEN BANGGAI KEPULAUAN DALAM MEWUJUDKAN PENGELOLAAN DANA DESA YANG EFEKTIF, EFISIEN, DAN AKUNTABEL - Yuhardi (Universitas Tadulako, 2024)
The purpose of this writing is to find out about the legal position of the Banggai Islands Regency Inspectorate in supervising the management of village funds and their effective, efficient and accountable use. The research method used is juridical and empirical writing. The legal position of the Banggai Islands Regency Inspectorate is that the Regent appoints Functional Officials who are tasked with carrying out internal supervision over the financial management of village funds so that their management can have a positive and significant impact on the financial management of village funds. The form of supervision that has been carried out by the Banggai Islands Regency Inspectorate is in the form of preventive (prevention) and repressive (enforcement) supervision in order to oversee effective, efficient and accountable management of village funds.